Neurobehavioral Outcome in Craniopharyngioma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The records of 20 children with craniopharyngioma seen between 1983 and 1995 were reviewed at the University of Colorado Health Sciences Center, Children's Hospital, and the Denver VA Medical Center, CO.